2021
DOI: 10.5696/2156-9614-11.29.210301
|View full text |Cite
|
Sign up to set email alerts
|

Underground Gold Miner Exposure to Noise, Diesel Particulate Matter and Crystalline Silica Dust

Abstract: Background. Respirable dust, diesel particulate matter, crystalline silica and noise pollution are the most common causes of health issues experienced by underground mine workers. Assessment of exposure levels in relation to standard regulatory body permissible levels is essential for the safety of mine workers. Objectives. The present study compared exposure levels of diesel particulate matter, crystalline silica dust and no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 20 publications
(32 reference statements)
0
8
0
Order By: Relevance
“…Factory workers and miners are a special group of workers with a relatively low overall level of education and are highly prone to suffering from mental health problems due to limited social support, excessive workload and irregular lifestyles, as well as occupational hazards such as noise and coal dust that they inevitably need to face in their working environment 18 19. Through a review of the literature, our group found that coal dust, crystalline silica and noise pollution were common causes of health problems for workers in underground mines 20. And, exposure to coal mine dust is a significant cause of pneumoconiosis in coal miners 21.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Factory workers and miners are a special group of workers with a relatively low overall level of education and are highly prone to suffering from mental health problems due to limited social support, excessive workload and irregular lifestyles, as well as occupational hazards such as noise and coal dust that they inevitably need to face in their working environment 18 19. Through a review of the literature, our group found that coal dust, crystalline silica and noise pollution were common causes of health problems for workers in underground mines 20. And, exposure to coal mine dust is a significant cause of pneumoconiosis in coal miners 21.…”
Section: Introductionmentioning
confidence: 98%
“… 18 19 Through a review of the literature, our group found that coal dust, crystalline silica and noise pollution were common causes of health problems for workers in underground mines. 20 And, exposure to coal mine dust is a significant cause of pneumoconiosis in coal miners. 21 In addition, asbestos is one of the major occupational hazards in the daily work of workers in the construction and automotive industries.…”
Section: Introductionmentioning
confidence: 99%
“…17 Through a review of the literature, our group found that coal dust, crystalline silica and noise pollution were common causes of health problems for workers in underground mines. 18 And, exposure to coal mine dust is a significant cause of pneumoconiosis in coal miners. 19 In addition, according to the China Public Health Data Centre, the top five provinces in China for human brucellosis incidence are Inner Mongolia, Xinjiang, Ningxia, Shanxi and Heilongjiang, with Xinjiang coming in second.…”
Section: Introductionmentioning
confidence: 99%
“…As of 2015, in China alone, the total number of pneumoconiosis cases among workers reached 72 000, with about 6000 deaths per year 17. Through a review of the literature, our group found that coal dust, crystalline silica and noise pollution were common causes of health problems for workers in underground mines 18. And, exposure to coal mine dust is a significant cause of pneumoconiosis in coal miners 19.…”
Section: Introductionmentioning
confidence: 99%
“…Chronic exposures to toxic substances, poor air quality and noise pollution have been highlighted as key mechanisms underlying these adverse health effects. This also applies to gold mining, independent of whether the metal is extracted in industrial mines [28][29][30][31] or through artisanal and small-scale gold mining [32,33]. Given the large health risks documented historically, major efforts have been made in recent years to establish environmental and occupational safety protocols including the establishment of the Occupational Safety and Health Authority (OSHA) in 2001 and the formulation of National Occupational Health and Safety Policy in 2010 [34].…”
Section: Introductionmentioning
confidence: 99%